2013
DOI: 10.1016/j.explore.2013.06.002
|View full text |Cite
|
Sign up to set email alerts
|

Family Medicine Residency Program Directors Attitudes and Knowledge of Family Medicine CAM Competencies

Abstract: Context Little is known about the incorporation of integrative medicine (IM) and complementary and alternative medicine (CAM) into family medicine residency programs. Objective The Society for Teachers of Family Medicine (STFM) approved a set of CAM/IM competencies for family medicine residencies. We hope to evaluate with an online survey tool, whether residency programs are implementing such competencies into their curriculum. We also hope to assess the knowledge and attitudes of Residency Directors (RDs) o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 19 publications
0
8
0
1
Order By: Relevance
“…Educating health-care professionals about CAM has an important role in ensuring patients’ safety and improving patients care. To that end, educational initiatives have been carried out in some countries and surveys coming from these countries have been showing a rising prevalence of CAM education in medical schools and residency programs [6066]. It was also reported that the registration in a CAM course can positively impact knowledge and attitude regarding CAM [67].…”
Section: Discussionmentioning
confidence: 99%
“…Educating health-care professionals about CAM has an important role in ensuring patients’ safety and improving patients care. To that end, educational initiatives have been carried out in some countries and surveys coming from these countries have been showing a rising prevalence of CAM education in medical schools and residency programs [6066]. It was also reported that the registration in a CAM course can positively impact knowledge and attitude regarding CAM [67].…”
Section: Discussionmentioning
confidence: 99%
“…This answers concerns expressed at both the MSE and GME level that one of the top barriers to integrating CAM content into the curriculum is finding time for it. 12,20 Limitations This study was limited by lack of a comparison group due to pre/ post single-group design. It is not clear that the changes in attitudes or intentions were attributable to the educational content itself.…”
Section: Discussionmentioning
confidence: 99%
“…16 Although GME on CAM has expanded in FMRs and improved resident knowledge in programs incorporating this training, other surveys show that only 5% of FM residents feel comfortable advising patients on CAM. [10][11][12]17 Less improvement has been made at the MSE level, with consequent reports that medical students are not comfortable counseling patients about CAM. 7,15,16 These data suggest that the US medical education system has done a poor job incorporating National Academy of Medicine recommendations.…”
Section: Original Articlesmentioning
confidence: 99%
See 2 more Smart Citations